Prevalence and Types of Prescribing Errors at A Public Tertiary Care Centre in Malaysia - Chang, Chee-Tao; Krishnasamy, Nalini; Olikh, Harveen Kaur; N, Kamaruddin; Chan, Huan-Keat; Hassali, Mohamed Azmi; Dawood, Omar Thanoon (Journal of Pharmacy Practice and Community Medicine)
Background: The current study aimed to determine the prevalence and types of prescribing errors at a public tertiary care center in Malaysia. Methods: This was a cross-sectional study, undertaken at the Pharmacy Department of the Raja Permaisuri Bainun Hospital, Ipoh. All the new prescriptions received during a four-week study period in 2012 were examined for prescribing errors. Results: Of the 11,009 prescriptions screened, 450 (4.1%) were found to have prescribing errors. The Emergency and Trauma Department (16.2%) recorded the highest number of errors. Omission and commission errors, respectively, constituted 56.4% and 40.2% of the cases, while 3.3% of the prescriptions contained illegible handwriting. Unspecified frequency (51.2%) and incorrect dosage (49.7%) were, respectively, the most common omission and commission errors. Conclusion: The findings confirm that prescribing error was common in the hospital. Efforts to reduce such errors, including the introduction of a system conducive to appropriate prescribing, are therefore warranted.
Keywords: Medication errors; Pharmacies; Tertiary care center; Drug-related side effects; Adverse reactions